Aktivitas Inhibitor Î±-Amilase Ekstrak Etanol Tanaman Brotowali (Tinospora crispa L.) - Pujiyanto, Sri; Wijanarka, W; Raharjo, Budi; Anggraeni, Via (Bioma : Berkala Ilmiah Biologi, 2019)
Brotowali plant (Tinospora crispa L.) is a traditional Indonesian medicinal plant which has many benefits including for diabetes drugs. Diabetes mellitus (DM) is a metabolic abnormality caused by an increase in blood sugar levels. The purpose of this study was to determine the activity of Î±-amylase inhibitors of Brotowali (T. crispa L.) ethanol extract of plants. Extraction is done by maceration followed by evaporation. The extract obtained was tested for Î±-amylase inhibitor activity. The Î±-amylase inhibition test is based on the breakdown of starch substrates into maltose and glucose which is then determined by spectrophotometer after administration of DNS. Tests are carried out on controls and samples. As a substrate is 0.5% starch solution in 100 ml of sterile aquades. The reaction mixture was incubated 25 Â° C for 10 minutes. The reaction is stopped by adding 2 ml of 3,5-dinitrosalicylic acid (DNS). All the mixed solutions are then heated to 100 Â° C for 5 minutes and allowed to cool. The change in color of the solution is then measured for its absorbance at a wavelength of 540 nm. As a comparison used a control test that did not use extract samples. The results of Î±-amylase inhibitor activity test showed that ethanol extract with a concentration of 1000 Î¼g / mL had the highest inhibitory activity value of 95.06% compared to extract concentration of 500 Î¼g / mL, 250 Î¼g / mL, 125 Î¼g / mL and 62.5 Î¼g / mL. The results of testing the effect of substrate concentration showed that 0.5% starch concentration had the highest inhibitory value of 9.52% compared to 2%, 1% and 0.25% concentrations